Slow dynamics of tryptophan-water networks in proteins - Fenwick, R. Bryn (J Am Chem Soc, 2018)
Water has a profound effect on the dynamics of biomolecules and governs many biological processes, leading to the concept that function is slaved to solvent dynamics within and surrounding the biomolecule. Protein conformational changes on the μs-ms timescales are frequently associated with protein function, but little is known about the behavior of protein-bound water on these timescales. Here we have used NMR relaxation dispersion measurements to probe the tryptophan indoles in the enzyme dihydrofolate reductase (DHFR). We find that during structural changes on the μs-ms timescale, large chemical shift changes are often observed for the NH proton on the indole ring, while relatively smaller chemical shift changes are observed for the ring nitrogen atom. Comparison with experimental chemical shifts and density functional theory-based chemical shift predictions show that during the structural change the tryptophan indole NHs remain bound to water, but the geometry of the protein-bound water networks change. These results establish that relaxation dispersion measurements can indirectly probe water dynamics and indicate that water can influence, or be influenced by, protein conformational changes on the μs-ms timescale. Our data show that structurally conserved bound water molecules can play a critical role in transmitting information between functionally important regions of the protein and provide evidence that internal protein motions can be coupled through the mediation of hydrogen-bonded water bound in the protein structure.